2002
DOI: 10.1159/000066183
|View full text |Cite
|
Sign up to set email alerts
|

Subclinically Dry Eyes in Urban Delhi: An Impact of Air Pollution?

Abstract: Purpose: To study the effects of air pollution on the eyes of persons staying in the metropolis of New Delhi. Materials and Methods: 400 healthy volunteers from within and outside the metropolis of Delhi were investigated for the presence of tear film abnormalities. All persons underwent slitlamp examination to rule out any ocular surface disorder. The tear break-up time (BUT) was assessed along with a Schirmer test and the tear lysozyme activity and the tear pH were determined. Results: Of the 210 persons sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0
6

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 6 publications
2
40
0
6
Order By: Relevance
“…The impact of urban pollution and environmental toxins on the ocular surface has been evaluated in a few case-control studies. These studies reported a high incidence of ocular discomfort, tear film instability, and ocular surface changes among individuals lived in highly polluted cities of the world (Table 4).Two studies in New Delhi compared the groups of individuals living inside and outside the metropolitan area (63) . A higher frequency of EDED findings with TFBUT <10 seconds, Schirmer Test (ST) <10 mm, and low lysozyme levels in tears were reported among the individuals living within the metropolitan area.…”
mentioning
confidence: 99%
“…The impact of urban pollution and environmental toxins on the ocular surface has been evaluated in a few case-control studies. These studies reported a high incidence of ocular discomfort, tear film instability, and ocular surface changes among individuals lived in highly polluted cities of the world (Table 4).Two studies in New Delhi compared the groups of individuals living inside and outside the metropolitan area (63) . A higher frequency of EDED findings with TFBUT <10 seconds, Schirmer Test (ST) <10 mm, and low lysozyme levels in tears were reported among the individuals living within the metropolitan area.…”
mentioning
confidence: 99%
“…Smoking, air pollution and drugs have been suggested as risk factors in various studies [2] [7] [11]. Smoking predisposes the eye to tear film instability by its direct irritant action on the eye and represent modifiable risk factors in dry eye causation.…”
Section: Discussionmentioning
confidence: 99%
“…These include no standardization of the type of patients selected for the study, dry eye questionnaires, objective tests and dry eye diagnostic criteria. In literature there are various risk factors for dry eye which include air pollution, smoking, low humidity, high temperature, sunlight exposure and drugs [2] [7]- [11].…”
Section: Introductionmentioning
confidence: 99%
“…What is believed to cause DES is the abnormality of the pre-ocular tear fi lm, a three-layered structure consisting (from posterior to anterior) of the mucous, aqueous, and the lipid layer. Various risk factors accounting for DES in literature include air pollution, cigarette smoking, low humidity, high temperature, sunlight exposure, and drugs (26)(27).…”
Section: Eye Surfacementioning
confidence: 99%
“…Gupta et al (26) described the effects of air pollution on the eyes of persons residing in New Delhi. Tear fi lm abnormalities were present in a large number of people staying within the city, in comparison to people living outside this area, who apparently had normal eyes.…”
Section: Eye Surfacementioning
confidence: 99%